COMPARISON OF THE EFFECTS OF FOCUS HARMONIC SCALPEL AND CONVENTIONAL HAEMOSTASIS ON PARATHYROID FUNCTION IN THYROID SURGERY - Xu, Sheng-Qian; Ma, Yi; Su, Hong-Wei; Cheng, Jian-Feng; Zhou, You-Xing (Journal of Ayub Medical College Abbottabad, 2019)
Background: Protection of parathyroid is very important in thyroid surgery. Our aim was to compare the effect of Focus Harmonic Scalpel and Conventional Haemostasis on parathyroid function in thyroid surgery. Methods: To analyse the clinical data of patients in our hospital from November 2011ï½žDecember 2015 retrospectively. Operations has been performed with Focus Harmonic Scalpel in thyroid surgery since May 2013. Seventy-four patients with nodular goitre constituted Harmonic Scalpel group and Conventional Haemostasis group, and so did 139 patients with thyroid papillary carcinoma. Clinical data were compared such as age, gender, thyroid volume, operation procedure, preoperative parathyroid hormone and serum calcium concentration between the two groups. The differences between the two groups were observed in serum calcium concentration, parathyroid hormone concentration, incidence of transient hypocalcaemia and hypoparathyroidism after operation. Results: The preoperative data showed no significant difference between Harmonic Scalpel group and Conventional Haemostasis group. No significant difference existed in postoperative clinic data at six a.m. the first day after operation between the two groups for patients with nodular goitre. The incidence of transient hypoparathyroidism and hypocalcaemia in Harmonic Scalpel group were less than that in Conventional Haemostasis group in thyroid surgery. Significant differences existed in the mean of serum calcium concentration and incidence of transient hypocalcaemia between the two groups for thyroid papillary carcinoma statistically. Conclusions: Focus Harmonic Scalpel has certain advantages than conventional Haemostasis in protecting parathyroid glands, reducing the incidence of transient hypoparathyroidism and hypocalcaemia in thyroid surgery, especially for patients with thyroid cancer. Keywords: Thyroidectomy; Focus Harmonic Scalpel; Hypoparathyroidism; Hypocalcaemia